2012
DOI: 10.1590/s0034-89102012000100021
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre atividade física e qualidade de vida em adultos

Abstract: OBJECTIVE:To summarize and analyze evidences of the association between physical activity and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
1
62

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(158 citation statements)
references
References 54 publications
6
89
1
62
Order By: Relevance
“…Many studies have 60-100% agreement of results using the 36-item and the 12-item short form health surveys developed for the Medical Outcome Study (MOS SF-36 and SF-12, respectively) and the WHO Quality of Life shorter version (WHOQoL-BREF); though with some inconclusive associations and lack of association occasionally. 44 The direction of the association across studies showed increased level of HRQoL with higher PA among healthy, unhealthy, and elderly individuals. 45,46 The variations in the findings of our study and previous studies were due to some possible reasons.…”
Section: Discussionmentioning
confidence: 96%
“…Many studies have 60-100% agreement of results using the 36-item and the 12-item short form health surveys developed for the Medical Outcome Study (MOS SF-36 and SF-12, respectively) and the WHO Quality of Life shorter version (WHOQoL-BREF); though with some inconclusive associations and lack of association occasionally. 44 The direction of the association across studies showed increased level of HRQoL with higher PA among healthy, unhealthy, and elderly individuals. 45,46 The variations in the findings of our study and previous studies were due to some possible reasons.…”
Section: Discussionmentioning
confidence: 96%
“…It is recommended that programs to encourage bicycling focus on strategies to guarantee access to this modality, such as decreasing the price of bicycles and equipment and focusing more on women and older adults. Recently several tools have been identified to help implement changes to the Brazilian context for making it more conducive for physical activity 39 . The findings from this study highlight the need for such changes in order to promote bicycling in the community.…”
Section: Discussionmentioning
confidence: 99%
“…O sexo feminino, histórico de depressão, a não participação em atividades sociais, as dificuldades de relacionamento e a falta de atividades de lazer foram associados à maior chance de quadros depressivos (Guerrero López et al, 2013;Kim & Roh, 2014;Pucci, Rech, Fermino, & Reis, 2012;Roh et al, 2010).…”
Section: Introductionunclassified